International law, international relations, and global governance - Ku, Charlotte, 1950- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2012)
"International Relations and International Law have developed in parallel but distinctly throughout the 20th Century. However in recent years there has been a recognition that their shared concerns in areas as diverse as the environment, transnational crime and terrorism, human rights and conflict resolution outweigh their disciplinary and methodological divergences. Law scholars have perhaps discovered the importance of understanding the behavior of actions in the international legal system and international relations scholars have re-discovered that objectives, including normative objectives, might influence choices and condition behavior. This new interest coincides with a general broadening of cross-disciplinary interests into history, sociology, philosophy, psychology, and economics for law and similar developments in international relations. The distinctive rationale for inquiry remains for both fields of study, but the need to move beyond description only in the case of law or analysis only in the case of politics has also fueled a need for new methodologies to understand the changing phenomenon of international life today. This book focuses on collaborative work within the disciplines of international law and international relations, to note sample efforts to collaborate, and to assess the cultivation of an interdisciplinary outlook. "--
"This book focuses on collaborative work within the disciplines of international law and international relations, to note sample efforts to collaborate, and to assess the cultivation of an interdisciplinary outlook"--
Points of departure -- International concerns and the international community of states -- The expanded international political and juridical arena -- International relations in a global context -- International law in the global environment -- Taking stock : global governance in a post-Westphalian order.
economic&political bookfair2016
Includes bibliographical references (p. [212]-214) and index.
Keywords: International law; International relations; POLITICAL SCIENCE / General; POLITICAL SCIENCE / History & Theory; POLITICAL SCIENCE / International Relations / General